The Use of Flipbooks Containing Local-Culture-Based Short Stories for Contextual Literary Education in Higher Education - Rosita, Farida Yufarlina; Suryanto, Edy; Rohmadi, Muhammad; Suhita, Raheni (Proceeding International Conference on Education, 2025)
Innovations in contextual learning, such as literature instruction at higher education, are necessary for the digital transformation of education. Students' respect, sensitivity, and comprehension of cultural values can all be strategically developed through literature rooted in the local culture. The purpose of the study is to describe the use of flipbooks based on local culture in contextual literature learning and examine students' responses and perceptions. The study employs a descriptive qualitative approach, with 31 students from the PGMI program at UIN Kiai Ageng Muhammad Besari Ponorogo who are enrolled in the Language and Literature Skills course as the subjects. In this study, the research data is the literary learning process using flipbooks based on local culture. Data collection was conducted through classroom observation, in-depth interviews, and the distribution of questionnaires to students. The questionnaire in this study was only used to support student response data in using flipbooks during learning. The results of the study indicate that flipbooks were used in three stages of learning: (a) introduction to the material, (b) discussion of the content of the short stories, and (c) analysis assignments. Students demonstrated high enthusiasm for using flipbooks, particularly due to their attractive format, ease of access, and the relevance and familiarity of local cultural values. The interactive features in the flipbooks further strengthened students' understanding of the cultural context of the stories. Thus, locally-based flipbook media can create a contextual, critical, and reflective literary learning experience while enhancing appreciation for cultural diversity.